Desarrollo de algoritmo de software para comunicación eficiente y de bajo consumo de potencia en red de sensores inalámbricos. - Vásquez-Espinoza, Marco Antonio (Instituto Tecnológico de Costa Rica, 2012)
The control of maturity and size of the banana is one of the most important challenges of fruit export companies to different markets of the world, due to this we have given it the task of implementing an electronic, self-sufficient and very low energy consumption showing the different variables of the fruit, as is the size and temperature but wirelessly. Moreover, being a system powered by a lithium battery and not rely on the power grid has incorporated a constant monitoring of battery level on the device to ensure continuous system state. The plate used for the implementation of the project is called Waspmote and has the features needed to sense the variables, it also has wireless data transmission and rechargeable lithium battery.
Proyecto de Graduación (Licenciatura en Ingeniería Electrónica) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Electrónica, 2012.
Keywords: Rebeca; Waspmote; Libelium; Zigbee; Consumo energético; Sensores inalámbricos